Three new species of Sandalodesmus Silvestri, 1902 from the last intact stretches of Atlantic Forest in Brazil (Polydesmida: Chelodesmidae: Sandalodesmini) - Figueiredo, Thiago D.; Iniesta, Luiz F.m.; Brescovit, Antonio D.; Bouzan, Rodrigo S. (Zootaxa, 2025)
Three new species of the millipede genus Sandalodesmus Silvestri, 1902 (Diplopoda: Polydesmida: Chelodesmidae) are described from the southeastern coast of Brazil: Sandalodesmus peruibe sp. nov., Sandalodesmus jureia sp. nov., and Sandalodesmus fandango sp. nov. These new species co-occur at the same locality: a protected area within the Atlantic Forest, Estação Ecológica Juréia-Itatins. They are morphologically distinct by the structure of their gonopods. In addition, a revised identification key to all known species of Sandalodesmus is provided.